2018
DOI: 10.1186/s12913-018-3448-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with self-care practice among adult diabetes patients in West Shoa Zone, Oromia Regional State, Ethiopia

Abstract: BackgroundDiabetes, a rising global health problem, requires continuous self-care practice to prevent acute and chronic complications. However, studies show that few diabetes patients practice the recommended self-care in Ethiopia. The aim of this study was to assess factors associated with self-care practice among adult diabetes patients in public hospitals of West Shoa Zone, Oromia Regional State, Ethiopia.MethodsIn this cross-sectional study, 257 diabetes patients (mean age 42.9 ± 14.6 years, 54.1% male) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
51
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 57 publications
14
51
3
1
Order By: Relevance
“…This demonstrates that patients with a longer duration of diabetes were more compliant with selfcare activities. This result of the association between duration and better self-care activities is consistent with the study conducted in Ethiopia, which found that a longer duration leads to improved awareness of the disease, which, in turn, is linked to increased self-efficacy [29].…”
Section: Discussionsupporting
confidence: 90%
“…This demonstrates that patients with a longer duration of diabetes were more compliant with selfcare activities. This result of the association between duration and better self-care activities is consistent with the study conducted in Ethiopia, which found that a longer duration leads to improved awareness of the disease, which, in turn, is linked to increased self-efficacy [29].…”
Section: Discussionsupporting
confidence: 90%
“…Diabetes is one of the major global health problems that require continuous self-care practices to prevent potential acute and long-term complications (11). Self-care practice is a cornerstone of diabetes management that can ensure the involvement of clients to promote their health and prevent further short and long term complications.…”
Section: Discussionmentioning
confidence: 99%
“…A total of nineteen studies yielding a total study population of 6595 was eligible and included for both qualitative and quantitative analyses. Amhara, Oromia, and Hareri regions contributed 26.3%(24-28), 21% (6,11,29,30), and 157% (2,7,31) to the total of included studies, respectively. Three regions:…”
Section: Characteristics Of Included Primary Studiesmentioning
confidence: 99%
See 2 more Smart Citations